2021
DOI: 10.26434/chemrxiv-2021-sr171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computation-informed optimization of Ni(PyC)₂ functionalization for noble gas separations

Abstract: Metal-organic frameworks (MOFs) are promising nanoporous materials for the adsorptive capture and separation of noble gases at room temperature. Among the numerous MOFs synthesized and tested for noble gas separations, Ni(PyC)₂ (PyC = pyridine-4-carboxylate) exhibits one of the highest xenon/krypton selectivities at room temperature. Like lead-optimization in drug discovery, here we aim to tune the chemistry of Ni(PyC)₂, by appending a functional group to its PyC ligands, to maximize its Xe/Kr selectivity. To … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A joint experimental computational work involving about 2 orders of magnitude less number of materials has recently been published. 63 Therefore, our work focuses on the elucidation of the potential improvement/deterioration in the separation performance of materials due to the grafting of the functional groups on high-performing bare MOFs but not determining separation performances of the entire >300,000 hypothetical MOFs which would be too costly.…”
Section: Resultsmentioning
confidence: 99%
“…A joint experimental computational work involving about 2 orders of magnitude less number of materials has recently been published. 63 Therefore, our work focuses on the elucidation of the potential improvement/deterioration in the separation performance of materials due to the grafting of the functional groups on high-performing bare MOFs but not determining separation performances of the entire >300,000 hypothetical MOFs which would be too costly.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown earlier that structure optimizations (and optimization settings) may lead to considerably different gas uptakes. 60 For instance, it has been shown earlier that while Xe at 298 K, 1 bar in experimentally determined structure of Ni(PyC) 2 matches that in one of its optimized counterparts (optimized with unit cell parameter constraints), it is overestimated by other optimized counterpart structures (optimized with unit cell angle constraints and no constraints). 60 Secondly, while the studied gas mixtures are assumed to be dry, in practice, they may include varying levels of humidity which can affect the separation performances (adsorption selectivity, membrane selectivity, gas permeability) of adsorbents and/or membranes.…”
Section: Chmentioning
confidence: 97%
“…60 For instance, it has been shown earlier that while Xe at 298 K, 1 bar in experimentally determined structure of Ni(PyC) 2 matches that in one of its optimized counterparts (optimized with unit cell parameter constraints), it is overestimated by other optimized counterpart structures (optimized with unit cell angle constraints and no constraints). 60 Secondly, while the studied gas mixtures are assumed to be dry, in practice, they may include varying levels of humidity which can affect the separation performances (adsorption selectivity, membrane selectivity, gas permeability) of adsorbents and/or membranes. 61 As an example, Daglar et al 61 demonstrated that the inclusion of H 2 O in CO 2 /N 2 mixture can hamper the adsorption and membrane selectivity together with gas permeabilities.…”
Section: Chmentioning
confidence: 97%